The importance of knowing the potential for cure among women newly diagnosed with breast cancer - Raja Lexshimi RG; Raijah A. Rahim (Penerbit UKM, 2006)
A diagnosis of breast cancer among Malaysian women causes many women to seek cure from different health bodies and is a common practice prevalent among Malaysian women. The objective of the study was to explore whether cure is an important information to women newly diagnosed with breast cancer, and to assess if the information on cure were influenced by variables such as ethnic group, age, level of education and social class. A survey design using a structured interview was adopted for this study and nine items of information were presented to 100 women newly diagnosed with breast cancer. Women were asked to choose which information is important and of priority. Thurstone Scaling method was used to produce rank orderings or profiles of information and scale values according to priority. An Analysis of Variance (ANOVA) and t-test was carried out to look at the differences between the mean scores. Information on the likelihood of cure obtained the highest priority. No significant differences were found in terms of educational level, social class, age and ethnic groups in relation to the information on cure. In conclusion, adequate information on cure is important and a priority to all women newly diagnosed with breast cancer, irrespective of ethnic group, age, level of education and social class. The findings of this study will be useful to health care professionals when providing information to women newly diagnosed with breast cancer